Safety of high-dose ivermectin: a systematic review and meta-analysis - Navarro, Miriam; Camprubí, Daniel; Requena-Méndez, Ana; Buonfrate, Dora; Giorli, Giovanni; Kamgno, Joseph; Gardon, Jacques; Boussinesq, Michel; Muñoz, Jose; Krolewiecki, Alejandro (Journal of antimicrobial chemotherapy, 2020)
Abstract Background Ivermectin is a key anthelmintic for the control of neglected tropical diseases. The main indications for population-level control with ivermectin through mass drug administration are onchocerciasis and lymphatic filariasis; however, there is interest in using higher, fixed-dose regimens for the control of scabies, soil-transmitted helminths and malaria. Safety data for these higher-dose regimens are needed. Methods A systematic literature review and meta-analysis on the safety and doses of ivermectin was conducted. Eligible studies reported patient-level data and, for the meta-analysis, clinical trials reporting data on doses ≥200 and ≥400 μg/kg were included. Incidence ratios were used to compare adverse events by severity and organ system affected. Results The systematic search identified six studies for inclusion, revealing no differences in the number of individuals experiencing adverse events. A descriptive analysis of these clinical trials for a variety of indications showed no difference in the severity of the adverse events between standard (up to 400 μg/kg) and higher doses of ivermectin. Organ system involvement only showed an increase in ocular events in the higher-dose group in one trial for the treatment of onchocerciasis, all of them transient and mild to moderate in intensity. Conclusions Although within this review the safety of high-dose ivermectin appears to be comparable to standard doses, there are not enough data to support a recommendation for its use in higher-than-approved doses. Ocular adverse events, despite being transient, are of concern in onchocerciasis patients. These data can inform programme managers and guide operational research activities as new approaches for the use of ivermectin are evaluated.